Lymph Node-Targeted Synthetically Glycosylated Antigen Leads to Antigen-Specific Immunological Tolerance - Maulloo, Chitavi D.; Cao, Shijie; Watkins, Elyse A.; Raczy, Michal M.; Solanki, Ani. S.; Nguyen, Mindy; Reda, Joseph W.; Shim, Ha-Na; Wilson, D. Scott; Swartz, Melody A.; Hubbell, Jeffrey A. (Frontiers in Immunology, 2021)
Inverse vaccines that tolerogenically target antigens to antigen-presenting cells (APCs) offer promise in prevention of immunity to allergens and protein drugs and treatment of autoimmunity. We have previously shown that targeting hepatic APCs through intravenous injection of synthetically glycosylated antigen leads to effective induction of antigen-specific immunological tolerance. Here, we demonstrate that targeting these glycoconjugates to lymph node (LN) APCs under homeostatic conditions leads to local and increased accumulation in the LNs compared to unmodified antigen and induces a tolerogenic state both locally and systemically. Subcutaneous administration directs the polymeric glycoconjugate to the draining LN, where the glycoconjugated antigen generates robust antigen-specific CD4+ and CD8+ T cell tolerance and hypo-responsiveness to antigenic challenge via a number of mechanisms, including clonal deletion, anergy of activated T cells, and expansion of regulatory T cells. Lag-3 up-regulation on CD4+ and CD8+ T cells represents an essential mechanism of suppression. Additionally, presentation of antigen released from the glycoconjugate to naïve T cells is mediated mainly by LN-resident CD8+ and CD11b+ dendritic cells. Thus, here we demonstrate that antigen targeting via synthetic glycosylation to impart affinity for APC scavenger receptors generates tolerance when LN dendritic cells are the cellular target.